Literature Review of COVID-19 Antivirus Activities Bioactive Compounds and Herbal Plant Extracts - Yulianis, Yulianis; Yulion Putra, Rizky; Putri Agustina, Nadiva (Rifa'Institute, 2023)
Introduction: Currently the world is being hit by a virus outbreak that causes symptoms of pneumonia, on December 31, 2019 China reported a mysterious case of pneumonia with no known cause. Objective: The purpose of this study was to look at bioactive compounds and extracts that have the potential as COVID-19 antivirals. Method: This research is a literature study derived from the PubMed and Science Direct databases using the Preparred Reporting Items for Systematic Reviews and Meta-analysis (PRISMA) method. Result and Discussion: In the results of the literature review, 22 articles were found that entered the inclusion criteria. The average extracts and compounds in pre-clinical data showed a very strong IC50 value with a value of <50 ug/ml, while in clinical trials, herbal plant products showed that they were anti-inflammatory and immunomodulatory. Conclusion: So, it can be concluded that natural product products from herbal plants have the potential as an antiviral for COVID-19